A study of push and pull factors influencing employee retention in education sector in China: Using PLS-SEM and multi-group analysis - Zhengda Yao; Juanjuan Zhang; Dejun Kang (PLoS ONE, 2026)
Employee retention remains a pressing issue and it reflects a key psychological decision-making outcome shaped by work-related stressors and organizational resources. Drawing on the Push-Pull framework, this study examines how pull factors (training and development, compensation, and empowerment) and push factors (job dissatisfaction, job burnout, and peer turnover influence) affect employee retention, while testing the moderating role of engagement. Using survey data from 568 educators in Guangdong Province, Partial Least Squares Structural Equation Modeling and Multi-Group Analysis were employed. Results show that pull factors positively predict employee retention, whereas push factors negatively affect it. Engagement moderates the relationship between training and development and employee retention. The multi-group analysis results indicate that only job burnout shows a significant difference between public and private schools. The findings are important for education policymakers and school administrators. Targeted retention policies that integrate material incentives and psychological engagement can help stabilize the teaching workforce.